Beracara Prodeo di Pengadilan Agama Gorontalo - Zumiyati S. Ibrahim (Al-Mizan (e-Journal), 2019)
The procedural process in a prodeo case in terms of the stages of the event is basically the same as the procedural process as usual cases, the only difference is that in the prodeo legal process must go through the first hearing or what is called an incidental trial, which is a trial held before the examination of the main case to determine whether it can be done prodeo or not. Obstacles or factors affecting the implementation of the prodeo legal process include litigants not understanding the law of prodeo procedures, one of the litigants deliberately hanging the case because he wants to make it difficult for his opponent, the residence of the opposing party outside the jurisdiction of the Gorontalo Religious Court and the cost of prodeo cases charged to the State through the List of Budget Implementation of the Religious Court.